Spatial and temporal control of mitochondrial H2O2 release in intact human cells. (11th February 2022) - Hoehne, Michaela Nicole; Jacobs, Lianne J H C; Lapacz, Kim Jasmin; Calabrese, Gaetano; Murschall, Lena Maria; Marker, Teresa; Kaul, Harshita; Trifunovic, Aleksandra; Morgan, Bruce; Fricker, Mark; Belousov, Vsevolod V; Riemer, Jan
Abstract: Hydrogen peroxide (H2 O2 ) has key signaling roles at physiological levels, while causing molecular damage at elevated concentrations. H2 O2 production by mitochondria is implicated in regulating processes inside and outside these organelles. However, it remains unclear whether and how mitochondria in intact cells release H2 O2 . Here, we employed a genetically encoded high‐affinity H2 O2 sensor, HyPer7, in mammalian tissue culture cells to investigate different modes of mitochondrial H2 O2 release. We found substantial heterogeneity of HyPer7 dynamics between individual cells. We further observed mitochondria‐released H2 O2 directly at the surface of the organelle and in the bulk cytosol, but not in the nucleus or at the plasma membrane, pointing to steep gradients emanating from mitochondria. Gradient formation is controlled by cytosolic peroxiredoxins, which act redundantly and with a substantial reserve capacity. Dynamic adaptation of cytosolic thioredoxin reductase levels during metabolic changes results in improved H2 O2 handling and explains previously observed differences between cell types. Our data suggest that H2 O2 ‐mediated signaling is initiated only in close proximity to mitochondria and under specific metabolic conditions. Synopsis: Mitochondria are main producers of H2 O2 in cells and its release is an important indicator of their functional state. Here, nutrients affecting mitochondrial metabolism and cytosolic antioxidative systems are found to modulate H2 O2 gradients and signaling in intact human cells. Mitochondrial H2 O2 can be detected in the cytosol in intact human cells, but not the nucleus or at the plasma membrane. Mitochondrial H2 O2 gradients are steep and controlled by peroxiredoxins 1 and 2. Peroxiredoxins 1 and 2 complement each other and are present with a substantial reserve capacity. Metabolism‐induced changes of reducing processes control peroxiredoxin activity. Abstract : A genetically‐encoded sensor shows how peroxiredoxins and thioredoxin reductase restrict H2 O2 signaling to the proximity of mitochondria and specific metabolic conditions.